Biotechnology and the small-scale farmer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Biotechnology for small-scale farmers in developing countries : analysis and assessment procedures edited by Joske F G Bunders 1990 232pp ISBN 90 6256 935 8 Pbk VU University Press De Boelelaan 1005 1081 HV Amsterdam THE NETHERLANDS